Effect of collagen packing and moisture content on leather stiffness. (February 2019) - Kelly, S.J.R.; Weinkamer, R.; Bertinetti, L.; Edmonds, R.L.; Sizeland, K.H.; Wells, H.C.; Fratzl, P.; Haverkamp, R.G.
Abstract: Applications for skin derived collagen materials, such as leather and acellular dermal matrices, usually require both strength and flexibility. In general, both the tensile modulus (which has an impact on flexibility) and strength are known to increase with fiber alignment, in the tensile direction, for practically all collagen-based tissues. The structural basis for flexibility in leather was investigated and the moisture content was varied. Small angle X-ray scattering was used to determine collagen fibril orientation, elongation and lateral intermolecular spacing in leather conditioned by different controlled humidity environments. Flexibility was measured by a three point bending test. Leather was prepared by tanning under biaxial loading to create leather with increased fibril alignment and thus strength, but this treatment also increased the stiffness. As collagen aligns, it not only strengthens the material but it also stiffens because tensile loading is then applied along the covalent chain of the collagen molecules, rather than at an angle to it. Here it has been shown that with higher moisture content greater flexibility of the material develops as water absorption inside collagen fibrils produces a larger lateral spacing between collagen molecules. It is suggested that water provides a lubricating effect in collagen fibrils, enabling greater freedom of movement and therefore greater flexibility. When collagen molecules align in the strain direction during tanning, leather stiffens not only by the fiber alignment itself but also because collagen molecules pack closer together, reducing the ability of the molecules to move relative to each other. Graphical abstract: